2021
DOI: 10.3390/nu13031031
|View full text |Cite
|
Sign up to set email alerts
|

Hypotensive and Hepatoprotective Properties of the Polysaccharide-Stabilized Foaming Composition Containing Hydrolysate of Whey Proteins

Abstract: Whey protein hydrolysates (WPHs) are one of the most promising sources of biofunctional peptides with such beneficial properties as antioxidant, antihypertensive, anti-inflammatory and others. WPHs also could be used as foaming agents for aerated products (e.g., milk shake type drinks). However, WPH alone has a bitter taste and foamed WPH should be stabilized by additional ingredients. Here, we present a composition including WPH and three polysaccharides—pumpkin pectin, sodium alginate and ι-carrageenan—used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Also enzymatic hydrolysis can be controlled by pH, temperature, time, and using low energy requirements, as well as being able to maintain functional properties such as solubility (Schaafsma, 2009). The enzymatic hydrolysis of whey has resulted in obtaining peptides with biological properties represented in the antioxidant activity that can be incorporated into the diet as a natural alternative to industrial antioxidants (Kruchinin et al, 2021).Over the past decades, studies have shown great interest in bioactive peptides derived from food for their role in disease control.…”
Section: Introductionmentioning
confidence: 99%
“…Also enzymatic hydrolysis can be controlled by pH, temperature, time, and using low energy requirements, as well as being able to maintain functional properties such as solubility (Schaafsma, 2009). The enzymatic hydrolysis of whey has resulted in obtaining peptides with biological properties represented in the antioxidant activity that can be incorporated into the diet as a natural alternative to industrial antioxidants (Kruchinin et al, 2021).Over the past decades, studies have shown great interest in bioactive peptides derived from food for their role in disease control.…”
Section: Introductionmentioning
confidence: 99%